Tissue-specific Role of CX3CR1 Expressing Immune Cells and Their Relationships with Human Disease - Lee, Myoungsoo; Lee, Yongsung; Song, Jihye; Lee, Junhyung; Chang, Sun-Young (Immune network, 2018)
Chemokine (C-X3-C motif) ligand 1 (CX3CL1, also known as fractalkine) and its receptor chemokine (C-X3-C motif) receptor 1 (CX3CR1) are widely expressed in immune cells and non-immune cells throughout organisms. However, their expression is mostly cell type-specific in each tissue. CX3CR1 expression can be found in monocytes, macrophages, dendritic cells, T cells, and natural killer (NK) cells. Interaction between CX3CL1 and CX3CR1 can mediate chemotaxis of immune cells according to concentration gradient of ligands. CX3CR1 expressing immune cells have a main role in either pro-inflammatory or anti-inflammatory response depending on environmental condition. In a given tissue such as bone marrow, brain, lung, liver, gut, and cancer, CX3CR1 expressing cells can maintain tissue homeostasis. Under pathologic conditions, however, CX3CR1 expressing cells can play a critical role in disease pathogenesis. Here, we discuss recent progresses of CX3CL1/CX3CR1 in major tissues and their relationships with human diseases.Chemokine (C-X3-C motif) ligand 1 (CX3CL1, also known as fractalkine) and its receptor chemokine (C-X3-C motif) receptor 1 (CX3CR1) are widely expressed in immune cells and non-immune cells throughout organisms. However, their expression is mostly cell type-specific in each tissue. CX3CR1 expression can be found in monocytes, macrophages, dendritic cells, T cells, and natural killer (NK) cells. Interaction between CX3CL1 and CX3CR1 can mediate chemotaxis of immune cells according to concentration gradient of ligands. CX3CR1 expressing immune cells have a main role in either pro-inflammatory or anti-inflammatory response depending on environmental condition. In a given tissue such as bone marrow, brain, lung, liver, gut, and cancer, CX3CR1 expressing cells can maintain tissue homeostasis. Under pathologic conditions, however, CX3CR1 expressing cells can play a critical role in disease pathogenesis. Here, we discuss recent progresses of CX3CL1/CX3CR1 in major tissues and their relationships with human diseases.